The Role of Training and Satisfaction to Increase Employee Retention in the Manufacturing Industry in Batam - Kusumo, Pradino; Mon, Muhammad Donal (Universitas Islam Kadiri, 2024)
Human Resources are a very important asset in a company. Without qualified Human Resources/HR, the company cannot run its business system. This research uses quantitative methods with research samples of manufacturing employees in Batamindo Batam Industrial Area. Questionnaires are distributed via Google form with 478 respondents were collected. The variables used in this research were the dependent variable, retention and turnover intention, the independent training, and the mediation was employee satisfaction. The results of the research stated that the effect of training on retention and turnover intention in manufacturing companies in Batamindo Industrial Area, Batam City with variables that mediate employee satisfaction. From the test results, the relationship between employee satisfaction and retention has a positive and significant influence. The relationship between employee satisfaction and turnover intention has a positive and significant influence. The relationship between training and employee satisfaction has a positive and significant impact. The relationship between training and retention has a positive and significant impact. The relationship between training and turnover intention has a positive and significant impact.